PENERAPAN MODEL PEMBELAJARAN AKTIF DALAM PEMBELAJARAN AKIDAH AKHLAK PESERTA DIDIK KELAS X MAN 1 KOTA MAKASSAR - Muh. Syahrul Ramadhan; Syamsuddin; Rosdiana; Muhammad Yahdi; Muhammad Qasim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of active learning models in Aqidah Akhlak learning for tenth grade students at MAN 1 Makassar City, identify supporting and inhibiting factors, and analyze the impact of the implementation on students. This study used a qualitative descriptive approach. The subjects of this study consisted of Aqidah Akhlak teachers, vice principal for curriculum affairs, and tenth grade students at MAN 1 Makassar City. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation, and conclusion drawing. The validity of the data was tested through source and technique triangulation. The results showed that the implementation of active learning models was carried out through group discussions, question and answer activities, presentations, and problem-based learning related to students’ daily lives. Teachers acted as facilitators who guided students to be more active during the learning process. The implementation of active learning had a positive impact on increasing students’ participation, confidence in expressing opinions, and understanding of Aqidah Akhlak material. Supporting factors included teacher competence, school policy support, and adequate learning facilities, while inhibiting factors included limited learning time and differences in students’ characteristics. Therefore, active learning models need to be continuously developed to improve the quality of Aqidah Akhlak learning.